2019
DOI: 10.24251/hicss.2019.509
|View full text |Cite
|
Sign up to set email alerts
|

DYNECOM: Augmenting Empathy in VR with Dyadic Synchrony Neurofeedback

Abstract: In a novel experimental setting, we augmented a variation of traditional compassion meditation with our custom built VR environment for multiple concurrent users. The system incorporates respiration and brainwave based biofeedback that enables responsiveness to the shared physiological states of the users. The presence of another user's avatar in the shared virtual space supported low level social interactions and provided active targets for evoked compassion. We enhanced interoception and the deep empathetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 30 publications
0
33
0
Order By: Relevance
“…Authors concluded "that intersubjective abilities and social cognition could be more easily cultivated in real contact with other people than through imaginary encounters, as common in single meditation practices" (Bornemann & Singer, 2013, p. 453). A recent study on empathy (Järvelä et al, 2019) supports this impression. Participants (pairs, not couples) generated compassionate feelings towards a non-active avatar (solitary condition) or to an active avatar representing their partner (dyadic condition) in virtual reality.…”
Section: Evidence From Kindness-based Interventionsmentioning
confidence: 81%
“…Authors concluded "that intersubjective abilities and social cognition could be more easily cultivated in real contact with other people than through imaginary encounters, as common in single meditation practices" (Bornemann & Singer, 2013, p. 453). A recent study on empathy (Järvelä et al, 2019) supports this impression. Participants (pairs, not couples) generated compassionate feelings towards a non-active avatar (solitary condition) or to an active avatar representing their partner (dyadic condition) in virtual reality.…”
Section: Evidence From Kindness-based Interventionsmentioning
confidence: 81%
“…Distributed [29], [3], [26], [27], [30], [31], [33], [41], [45], [58], [60], [61], [63], [65], [70], [85], [94], [95], [107], [109], [113], [82], [125], [135] [52], [67], [73], [72], [80], [78], [75], [81],…”
Section: Physical Contextmentioning
confidence: 99%
“…In 12 studies, users only received feedback about states of co-users and not their own [3,29,30,45,55,65,87,91,94,110,125,133], while in four studies only aggregated measures of physiology were shown to both players [83,100,107,142]. Six studies combined the sharing physiology of all users with additional aggregated measures like average metrics [17] and synchrony level between users [46,60,61,82,113]. One study manipulated both receiving biofeedback from self and others, instead of only others' [40].…”
Section: Articulating the Physiological-social Interaction Spacementioning
confidence: 99%
See 2 more Smart Citations